Pengaruh Kepemilikan Asing, Kepemilikan Institusional dan Leverage terhadap Pengungkapan Corporate Social Responsibility - Yani, Ni Putu Tista Paradiva; Suputra, I Dewa Gede Dharma (E-Jurnal Akuntansi; Vol 30 No 5 (2020)DO - 10.24843/EJA.2020.v30.i05.p10, 2020)
The purpose of this study was to determine the effect of foreign ownership, institutional ownership, and leverage on corporate social responsibility disclosure. The theory used is stakeholder theory. This research was conducted at the Indonesia Stock Exchange (IDX) in the mining company for the period of 2016-2018. Data analysis technique used is multiple linear regression analysis. The method of determining the sample non probability sampling with purposive sampling technique. The number of samples was 51 of 17 companies with a three-year observation period. The analysis shows that foreign ownership, ownership, institutional influence on the disclosure of corporate social responsibility, while leverage does not affect the disclosure of corporate social responsibility. Keywords: Corporate Social Responsibility; Foreign Ownership; Institutional Ownership; and Leverage.